2017
DOI: 10.2139/ssrn.2996506
|View full text |Cite
|
Sign up to set email alerts
|

Female Brain Drain in Poland and Germany: New Perspectives for Research

Abstract: The publication was prepared within the project "Brain drain/brain gain: Polish-German challenges and perspectives-Focus on the gender aspects of labour migration from 1989" with financial support from the Polish-German Foundation for Science and The Foundation for Polish-German Cooperation. The opinions expressed in this publication are those of the authors and do not necessarily reflect the views of CASE Network. "CASE Reports" is a continuation of a "CASE Network Studies & Analyses" series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Many studies [22][23] have shown that gender inequality hinders economic growth and that, on the contrary, gender equality, as well as a high level of women's participation in the labor market, contribute to economic development. The world economic forum demonstrated the relationship between GDP per capita and global gender gap index, showing the links between human development, gender gap and global competitiveness, identifying correlation between these three indicators, and demonstrating that women's empowerment and reducing gender inequality contribute to economic growth [16].Moreover, in a study by Beaumont Karolina et al (2017) [16] found that other gender issues, such as the pay gap and access to childcare, are linked to brain drain among women. It was also noted that gender inequality in the sending country can be a driving factor for women and, conversely, that improved gender policies limit brain drain and its negative consequences.…”
Section: Opening Of Borders Between Eu Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies [22][23] have shown that gender inequality hinders economic growth and that, on the contrary, gender equality, as well as a high level of women's participation in the labor market, contribute to economic development. The world economic forum demonstrated the relationship between GDP per capita and global gender gap index, showing the links between human development, gender gap and global competitiveness, identifying correlation between these three indicators, and demonstrating that women's empowerment and reducing gender inequality contribute to economic growth [16].Moreover, in a study by Beaumont Karolina et al (2017) [16] found that other gender issues, such as the pay gap and access to childcare, are linked to brain drain among women. It was also noted that gender inequality in the sending country can be a driving factor for women and, conversely, that improved gender policies limit brain drain and its negative consequences.…”
Section: Opening Of Borders Between Eu Countriesmentioning
confidence: 99%
“…These high numbers of the Diaspora are a reflection of Poland's turbulent history. Since 1950, about 2.5 million poles have moved to Germany, and now 6.5% of all foreigners living in Germany are poles, among whom the number of women is very high [15][16].…”
Section: Increasing Feminization Of Migration Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ακόμη, απαντώνται οι όροι «επιστροφή εγκεφάλων» ή «αντίστροφη διαρροή εγκεφάλων» ("brain return" ή "reverse brain drain"), που αφορούν την επιστροφή των μεταναστών με υψηλό επίπεδο εκπαίδευσης στις χώρες καταγωγής τους (Λαμπριανίδης 2011: 29, Gaillard και Gaillard 1998, ο όρος «κυκλοφορία εγκεφάλων» ("brain circulation"), που αφορά τη μετανάστευση των πτυχιούχων μεταξύ των ανεπτυγμένων χωρών, όπως μεταξύ των χωρών της ΕΕ (Λαμπριανίδης 2011: 19&343, Λαμπριανίδης 2014: 177) καθώς και ο όρος «εισροή/κέρδος εγκεφάλων» ("brain gain", βλ. Straubhaar 2000, Schellinger 2015a, Meyer και Brown 1999: 11, Iravani 2011: 284, Κουγιού 2016, Wahba 2014, Stark et al 1997, Ha et al 2016, Beaumont et. al.…”
Section: μεθοδολογία της έρευναςunclassified
“…Στην πραγματικότητα, όμως, αυτή η ευκολία κυκλοφορίας εντός της ΕΕ είναι πιθανό να μην οδηγεί πάντα σε αμοιβαία επωφελής καταστάσεις (win-win situation) για όλα τα συμβαλλόμενα μέρη, καθώς μπορεί να συμβάλει στην ενίσχυση των προβλημάτων που αντιμετωπίζουν οι κατ' εξοχήν χώρες αποστολής μεταναστών όπως είναι πχ. η Πολωνία(Murdoch και Hutyra 2008, Beaumont et al 2017) και η Ρουμανία (βλ.Alexe et.al. 2011, Goschin et.…”
unclassified